Dynamic impacts of commodity flow disruptions in inland waterway networks. (November 2015) - Pant, Raghav; Barker, Kash; Landers, Thomas L.
Highlights: We use dynamic multi-regional interdependency models for studying inland port disruptions. We build simulation models for normal and disruptive waterway network operations. Our work quantifies impact of multi-regional, multi-industry damage on interdependent economies. The study of multi-regional, multi-industry impacts benefit the preparedness process for important waterway infrastructure. Abstract: Freight and passenger transport in the US is projected to increase substantially by 2035 making a strong case for greater usage of the inland waterway barge transport. Inland waterway networks constitute an important component of the US multi-modal transport infrastructure spanning 25, 000 miles of navigable routes across 38 states. Risk-based preparedness planning for inland waterway networks requires a means to assess the interdependent impacts associated with closures to inland waterway infrastructure. This study proposes a dynamic framework to assess multi-regional, multi-industry losses due to disruptions on the waterway networks, including ports and waterway links. We investigate simulation-driven disruptive scenarios, such as dock closures, that affect daily commerce across the waterway network and integrate with a dynamic interdependency model to quantify the effect of disruptions on industry inoperability across multiple regions and multiple industries. We implement our framework with a data-driven case study of the operations at the Port of Catoosa on the McClellan–Kerr Arkansas River branch of the Mississippi River Navigation System. Resulting dock-specific, industry-specific, and region-specific insights can guide preparedness decision making.